Tabus Linguísticos na região Sul do Brasil: um estudo com base em dados geolinguísticos - KAMILLA DE LIMA VIEIRA (2023)
ABSTRACT This work analyzes names for "devil"; "ghost" and "spell" in the Southern Region of Brazil, based on lexical data from the ALiB Project (Linguistic Atlas of Brazil) provided by speakers from the capitals and interior of the states of Paraná, Santa Catarina and Rio Grande do Sul, as answers to three questions from the Semantic-lexical Questionnaire (QSL) in the thematic area of religion and beliefs: 147 - "God is in heaven and he is in hell. ."; 148 - "What do some people say they have seen at night, in cemeteries or in houses, that they say is from another world?" and 149 - "What do some people do to harm someone and put at crossroads, for example?" (National Committee..., 2001, p. 33). To this end, the corpus of the ALiB Project documented in 44 locations in the Southern Region was consulted through surveys carried out with 308 informants, 72 from the capitals and 236 from inland locations, male and female; two age groups (18-30 years and 50-65 years), with two levels of education in the capitals (incomplete elementary school and higher education) and elementary school in the inland locations, born and raised in the locality. The study is based on the theoretical- methodological foundations of Pluridimensional Dialectology, Geolinguistics (Ferreira; Cardoso, 1994; Cardoso, 2010; Cardoso; Mota, 2003), complemented by theoretical assumptions from Ethnolinguistics (Sapir, 1971; Coseriu, 1978; Casado Velarde, 1991; Gomes-Dias, 2019), Linguistic Anthropology (Duranti, 2000) and foundations on linguistic taboos and euphemism (Guérios, 1979; Ullmann, 1964; Cassirer, 1972; Crespo-Fernandez, 2005). The general objective of this work is to carry out a study of the lexical units used by speakers in the Southern Region of Brazil which highlight the values, beliefs and culture of speakers in the interior and capitals of Brazil. The specific objectives are: i) to identify, describe and analyze the lexical items which name referents related to the thematic area of religion and beliefs in the interior and capitals of the Southern Region of Brazil; ii) to see to what extent socio-historical and cultural factors in the locations surveyed influence speakers' lexical choices; iii) to examine the lexical units catalogued from the diatopic, diastratic, diagenerational, diasexual and lexical-semantic points of view; iv) to analyze the lexical forms that are configured as taboo and euphemistic, as well as the different substitutive resources for the word- tabu used by speakers. For question 147/QSL/ALiB, 37 names were documented, with the most productive being devil, capeta, demônio, satanás and lúcifer; question 148/QSL/ALiB, in turn, led to the recording of 30 names, with a predominance of haunting, ghost, visagem, alma penada, espírito, alma and vulto; question 149/QSL/ALiB, in turn, generated 27 answers, with the most frequent and validated being feitiço, despacho and trabalho. In addition to the diatopic perspective, the data was analyzed according to social variables and from a lexical-semantic perspective. The study also highlights taboo names such as Satan, Beelzebub, Devil and Lucifer; ghost, spirit, haunting, visage, vision and shadow; witchcraft and black magic. In this area, the study attested to the influences of the European Christian imaginary coming from the colonizers and immigrants who, bringing their cultures and traditions, attributed to everything that was different the figure of "evil", which triggered, in a way, religious prejudices rooted in some of the denominations documented. In this sense, the purpose of this study was to contribute to the understanding of aspects of the lexicon that reveal religious myths and superstitions, as well as to provide reflections with a view to "demythologizing" denominations of the phenomena covered by the study that populate the popular imagination of southern speakers. Keywords: Lexicon. Religions and Beliefs. ALiB Project. Linguistic taboos. Southern Brazil.